The electronic excited states of ethylene with large-amplitude deformations: a dynamical symmetry group investigation - Lasorne, Benjamin; Robb, Michael A.; Meyer, Hans-Dieter; Gatti, F. (Chemical physics, 2010)
We show that the lowest manifold of electronic states of ethylene (ethene, C2H4) can be described correctly with a complete active space of 17 quasidiabatic configurations built on state-averaged orbitals. This space is stable upon large-amplitude deformations, such as torsion, pyramidalization, CC stretching and HCH bending. The properties of the nuclear coordinates and valence and Rydberg electronic states are investigated within the framework of nuclear-permutation-inversion group theory. This systematic analysis is compared to a previous model of the valence states of ethylene (R.P. Krawczyk, A. Viel, U. Manthe, W. Domcke, J. Chem. Phys. 119 (2003) 1397). Our approach is intended to be generalized to the non-adiabatic photochemistry of organic molecules where large-amplitude deformations require global vibronic Hamiltonian models to be expressed in terms of simple functions of polyspherical valence coordinates.